Segmental eczema: within the spectrum of mosaic spongiotic dermatitides. - Torchia, D.; Schachner, L.A. (European Journal of Pediatric Dermatology, 2011)
Like many other polygenic skin disorders, atopic dermatitis may present in a segmental pattern, probably expression of cutaneous mosaicism. After a brief case vignette, we reviewed systematically and critically the literature on segmental spongiotic dermatitides. We identified 70 reported cases of segmental spongiotic dermatitis (31 of segmental eczema/non otherwise specified dermatitis, 34 of so-called "blaschkitis" and 5 of drug-induced dermatitis). On the basis of current evidence, segmental atopic dermatitis and blaschkitis appear to be clinically and etiopathogenically distinct conditions.